Description Of Low Birth Baby Events In H.A Sulthan Dg Radja Hospital - Andi Nurlaily; Marwidah (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2018)
Infant mortality is the first indicator in determining the child’s health status. Low birth weight babies can be caused by several factors, namely maternal factors and fetal factors, while other factors are placental factors. The purpose of this study is to describe the incidence of low birth weight infants in RSUD H.A Sulthan Dg Radja Kabupaten Bulukumba Tahun 2017 that’s is 1.830 babies with a sample of 65 BBLR and 65 babies who are not BBLR, sampling in this study was carried out in 2 ways, namely by random sampling technique for non BBLR infants and total sampling technique for BBLR infants.BBLR infants showed that 20 to 35 years old are 51 people (78,5%) for BBLR. Whereas 46 people (70,8%) who are not low LBW are more dominant than <20 years old and >35 years old while for parity, there are 33 people (50,8%) who are LBW and 20 people (30,8%) who are LBW, the number of multiparas is 29 people (44,6%) who are LBW and those who are not LBW are 39 people (60,9%) and grand multipara 3 people (4,6%) are LBW and those who are not LBW are 6 people (9,2%) with a total of 130 respondents. Conclusions in the research conducted in RSUD H.A Sulthan Dg Radja from the data of 65 infants of low birth weight found that the most dominant were mothers with primiparous parity and for the date of 65 infants who were not BBLR found that the most dominant age was low risk, for the most dominant parity, namely mothers with multiparous parity. Suggestions as maternal for consideration and reference in the prevention of BBLR, as a scientific contribution and maternal for future researchers.